2008
DOI: 10.1016/j.cub.2008.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of the BOLD fMRI Signal in Awake Monkeys

Abstract: The persistent coupling of the BOLD signal to the field potential when LFP and MUA have different time evolutions suggests that BOLD is primarily determined by the local processing of inputs in a given cortical area. In the alert animal the largest portion of the BOLD signal's variance is explained by an LFP range (20-60 Hz) that is most likely related to neuromodulation. Finally, the similarity of the results in alert and anesthetized subjects indicates that at least in V1 anesthesia is not a confounding fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
423
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 526 publications
(466 citation statements)
references
References 54 publications
37
423
6
Order By: Relevance
“…Neuroimaging of spontaneous infraslow activity has been the focus of tremendous research interest, but has typically relied upon imaging modalities that indirectly reflect neuronal activity [45][46][47][48] and have thus raised questions about the underlying nature and interpretation of these data 22,36 . Innovative efforts to directly assess the neurophysiological basis of fMRI BOLD signal fluctuations have revealed much about the best electrophysiological correlates of these signals, but these approaches require specialized recording equipment and technical analysis to remove electrical artifacts and are limited in their spatial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging of spontaneous infraslow activity has been the focus of tremendous research interest, but has typically relied upon imaging modalities that indirectly reflect neuronal activity [45][46][47][48] and have thus raised questions about the underlying nature and interpretation of these data 22,36 . Innovative efforts to directly assess the neurophysiological basis of fMRI BOLD signal fluctuations have revealed much about the best electrophysiological correlates of these signals, but these approaches require specialized recording equipment and technical analysis to remove electrical artifacts and are limited in their spatial coverage.…”
Section: Discussionmentioning
confidence: 99%
“…An additional hypothetical mechanism can be associated with the different amplitude of fMRI response in human and monkey experiments. BOLD fMRI responses and neural activity is smaller during anesthesia then in the alert condition (Goense and Logothetis, 2008;Martin et al, 2006). Dependent on the extent of the stimulus (e.g.…”
Section: Hypothetical Mechanism Underlying Negative Bold Contrastmentioning
confidence: 96%
“…This calculation is in general agreement with experiments based upon simultaneous recording of electrophysiology and BOLD. Combined electrophysiology and fMRI is relatively popular to explore the coupling between the neuronal activity and haemodynamic response, although most literature is limited to the study of experimental animals (Logothetis et al, 2001, Shmuel et al, 2006, Goense and Logothetis, 2008, Goloshevsky et al, 2008. Multiple studies have demonstrated that the BOLD response is more closely coupled to LFP rather than MUA (Logothetis et al, 2001, Niessing et al, 2005, Shmuel et al, 2006, Goense and Logothetis, 2008.…”
Section: Boldmentioning
confidence: 99%